2005
DOI: 10.1152/ajpheart.00729.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension attenuates cell-to-cell communication in hamster retractor muscle feed arteries

Abstract: . Hypertension attenuates cell-tocell communication in hamster retractor muscle feed arteries. Am J Physiol Heart Circ Physiol 288: H861-H870, 2005. First published October 14, 2004 doi:10.1152/ajpheart.00729.2004.-This study examined whether hypertension attenuated cell-to-cell communication in skeletal muscle resistance arteries. Briefly, arteries feeding the retractor muscle of normotensive and hypertensive hamsters were cannulated, pressurized, and superfused with a physiological saline solution. Cell-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 43 publications
3
32
1
1
Order By: Relevance
“…75,108 -112 Thus, conduction of vasomotor responses represents an attractive mechanism by which vascular gap junctions could participate in the control of arterial blood pressure. Consistent with this idea, conducted vasodilation is impaired in spontaneously hypertensive hamsters, 113,114 SHRs, 39,56 and Cx40 knockout animals. 59 It is worth noting that theoretical considerations suggest that gap junctional modulation of conduction of vasomotor signals may also play a role in the long-term control of peripheral resistance.…”
Section: A Role For Conducted Responses In the Pathogenesis Of Hypertsupporting
confidence: 54%
“…75,108 -112 Thus, conduction of vasomotor responses represents an attractive mechanism by which vascular gap junctions could participate in the control of arterial blood pressure. Consistent with this idea, conducted vasodilation is impaired in spontaneously hypertensive hamsters, 113,114 SHRs, 39,56 and Cx40 knockout animals. 59 It is worth noting that theoretical considerations suggest that gap junctional modulation of conduction of vasomotor signals may also play a role in the long-term control of peripheral resistance.…”
Section: A Role For Conducted Responses In the Pathogenesis Of Hypertsupporting
confidence: 54%
“…Recently, this important endothelial function has been shown to be altered under pathological conditions. In chronically hypertensive animals, the conduction of dilations initiated by ACh was attenuated in vivo [32] as well as in isolated vessels [33]. Furthermore, it is well demonstrated that hypercholesterolemia alters the composition of Cx proteins in large conducting arteries in the area of plaque formation [28] but also in areas completely lacking signs of morphological changes [27].…”
Section: Discussionmentioning
confidence: 99%
“…8). In support of the importance of coordination and integration of vasomotor tone in the control of arterial blood pressure (37, 55, 56) and structural adaptation of the microvascular network (152,153), conduction of vasodilator responses has been found to be impaired in spontaneously hypertensive hamsters (110,111) and SHRs (72).…”
Section: Fig 7 Connexin-based Channels Likely To Be Involved In Neumentioning
confidence: 98%